Subjective well-being among women with disabilities - Fatwa Tentama; Nina Zulida Situmorang; Muthmainah Muthmainah (International Journal of Public Health Science (IJPHS), 2021)
Women with disabilities are individuals who have double vulnerabilities. These vulnerabilities are arguably resulting from their condition as disabled persons and their status as a woman. Both women with innate disabilities factors and accident factors have a similarly negative view of their condition. This study aimed to describe subjective well-being in women with disabilities. The research method used was qualitative phenomenology. The data was obtained through semi-structured interviews. This study included six women with disabilities (visually impaired), aged between 20 to 30 years who lived in Yogyakarta and status as a graduate student. The data from interviews were analyzed with thematic analysis. The results showed that subjective well-being in women with disabilities was influenced by cognitive component (life satisfaction), which was indicated by self-acceptance, positive social relations, and perceived gratitude. Besides, the affective component also played a role. This component included positive affect, which was indicated by a sense of attention that the participant received, a feeling of excitement, pleasure, and a feeling of pride. Negative affect was indicated by feelings of sadness because of past negative relationships and feelings of disappointment.